Autoinflammatory Bone Diseases - Fatih Haşlak; Nergis Akay; Ümit Gül; Aybüke Günalp; Elif Kılıç Könte; Sezgin Şahin; Özgür Kasapçopur (Balkan Medical Journal)
Autoinflammatory bone diseases (AIBDs) constitute a recently identified subset of autoinflammatory diseases. These conditions are characterized by an exaggerated inflammatory response in the bones without any apparent etiology. Inflammatory bone lesions associated with AIBDs exhibit chronic inflammation, are typically culture-negative, and do not exhibit discernible microorganisms on histopathological examination. The most common and representative AIBD is chronic non-bacterial osteomyelitis (CNO), which is also known as chronic recurrent multifocal osteomyelitis. Another variant of CNO, which is typically observed in older teenagers or adults, is known as synovitis, acne, hyperostosis, pustulosis, osteitis syndrome. This condition is distinguished by its notable skin manifestations. Advancements in genetic research have led to the identification of three novel monogenic subtypes within the category of AIBDs. These include Majeed syndrome, pyogenic arthritis, pyoderma gangrenosum, and acne syndrome, and interleukin-1 receptor antagonist deficiency syndrome. Another monogenic AIBD, called cherubism, affects only the maxilla and mandible. Data on the diagnosis and treatment of these rare diseases are extremely limited. However, if not diagnosed and treated promptly, it can result in significant complications, including severe disability and mortality. Thus, it is imperative to maintain a high level of clinical awareness of these diseases. These rare diagnoses should be considered in patients with musculoskeletal complaints in whom no specific etiology can be identified or in patients with systemic manifestations such as cutaneous and gastrointestinal symptoms or fever. In such patients, the diagnostic process, which encompasses imaging and genetic studies, should be initiated promptly.